Description of a new Limnophora species from Bulgaria (Diptera: Muscidae) - Zielke, Eberhard (Contributions to Entomology = Beiträge zur Entomologie, 2017)
Limnophora ljubomirovi spec. nov. with slightly curved wing-vein M1 and long plumose hairs of arista is described from Bulgaria and compared with similar species of the genus. Nomenclatural Acts Limnophora ljubomirovi spec. nov. – urn:lsid:zoobank.org:act:BC851ACE-FCBA-482F-800D-70177499A33A